Effective use of fondaparinux in patient with unresponsiveness to nadroparin - Hartinger, Jan Miroslav; Svobodová, Alžběta; Malíková, Ivana; Šachl, Robert; Slanař, Ondřej (Journal of clinical pharmacy and therapeutics, 2021)
WHAT IS KNOWN AND OBJECTIVE: Fondaparinux exhibits a similar mechanism of action as LMWH. Since both of these drugs bind to antithrombin and increase its affinity to factor Xa, fondaparinux is not expected to be an effective alternative anticoagulant to LMWH in case of LMWH resistance. CASE SUMMARY: We report on a case of effective anticoagulation using fondaparinux following total unresponsiveness to high doses of nadroparin administered twice daily, as confirmed via repeated anti-Xa measurements. The antithrombin levels were within the normal range. WHAT IS NEW AND CONCLUSION: To the best of our knowledge, this is the first report of the effective use of fondaparinux in the case of unresponsiveness to LMWH.
Keywords: antikoagulancia; Nadroparin; Anticoagulants; pentasaccharide; Blood Coagulation; fondaparinux; lidé; heparin resistance; antithrombin; anticoagulation; low molecular weight heparin; Male; Aged; Fondaparinux; nadroparin; heparin nízkomolekulární; senioři; mužské pohlaví; hemokoagulace; Heparin, Low-Molecular-Weight; Humans